Domestic Devotions in Early Modern Italy - Corry, Maya; Faini , Marco; Meneghin, Alessia (Intersections, 2018)
Domestic Devotions in Early Modern Italy illuminates the vibrancy of spiritual beliefs and practices which profoundly shaped family life in this era. Scholarship on Catholicism has tended to focus on institutions, but the home was the site of religious instruction and reading, prayer and meditation, communal worship, multi-sensory devotions, contemplation of religious images and the performance of rituals, as well as extraordinary events such as miracles. Drawing on a wide range of sources, this volume affirms the central place of the household to spiritual life and reveals the myriad ways in which devotion met domestic needs. The seventeen essays encompass religious history, the histories of art and architecture, material culture, musicology, literary history, and social and cultural history.